Optimization of Esterification in the Synthesis of Surfactants Feedstock from Polar Lipid Fraction of Crude Palm Oil - Muzakhar, Syah Sultan Ali; Assidiqie, Gloria Islamy; Siregar, Albar Sutan Bahari; Aparamarta, Hakun Wirasasista; Fahmi, Fahmi; Gunawan, Setiyo (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
Surfactants (monoglycerides and diglycerides) can be obtained by converting triglycerides and glycerol with a NaOH as catalyst. A low free fatty acids (FFA) content starting material is needed due to the formation of soap as side product. The aim of this research was to optimize the esterification of (Polar lipid fraction) PLF to eliminate the FFA content with ZnCl2 as catalyst. Optimization was conducted on the variables of duration (ranging from 40 to 80 min) and reaction temperature (210–250°C) using the Response Surface Method with Central Composite Design with starting FFA content of 28.4%. It was found that an FFA content of 0.285% and a yield of 97.25% were achieved at a temperature of 258.3°C and a heating duration of 59.71 min. Moreover, the influence of temperature and heating duration during the esterification reaction on the FFA content was highly significant, as indicated by the P-Value of 0.00000102. Meanwhile, the influence of temperature and heating duration during the esterification reaction on the yield is not significant (P-Value = 0.130).